Survey of arctic bird migration and staging areas at the White Sea, in the autumns of 1999 and 2004 - Lehikoinen, Aleksi; Kondratyev, Alexander V.; Asanti, Timo; Gustafsson, Esko; Lamminsalo, Olli; Lapshin, Nikolay V.; Pessa, Jorma; Rusanen, Pekka (Finnish Environment Institute, 2013)
Finnish Environment Institute organized two ornithological expeditions to the White Sea, between 21st September and 10th October 1999, and between 21st September and 10th October 2004. The main aim of these expeditions was to map the most important staging areas for the migrating arctic birds at the White Sea. Several internationally important staging areas were found at the White Sea. Transect line counts at sea showed that the densities of birds outside these areas were smaller. During the expeditions a lot of data collected about the migration, daily rhythm, directions and routes of the migration, intensity, timing and the age and sex of the birds. Clear differences between species were noticed in the dynamics, directions of routes and intensity. Some of the species migrate on a wide front and others follow the coastal lines. The expedition was carried out by vessel. Compared to aerial surveys, which are also used for mapping of staging areas, vessel is cheaper. Vessel surveys allow more time for observing for instance birds which are sensitive or few in numbers. On the other hand a vessel is slow and shallow areas, which are important staging areas for waterfowl, are inaccessible. Aerial surveys make it possible to cover large areas and to find the most important staging areas for arctic waterfowl.